2015
DOI: 10.1097/nnr.0000000000000076
|View full text |Cite
|
Sign up to set email alerts
|

Multilevel Drivers of Human Immunodeficiency Virus/Acquired Immune Deficiency Syndrome Among Black Philadelphians

Abstract: Background Unequal HIV/AIDS distribution is influenced by certain social and structural contexts that facilitate HIV transmission and concentrate HIV in disease epicenters. Thus, one of the first steps in designing effective community-level HIV/AIDS initiatives is to disentangle the influence of individual, social, and structural factors on HIV risk. Combining ethnographic methodology with geographic information systems (GIS) mapping can allow for a complex exploration of multilevel factors within communities … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 37 publications
1
8
0
Order By: Relevance
“…It is possible that the variation across studies may be ascribed to different historical and contextual characteristics not easily measured through quantitative markers and/or not necessarily replicable across communities. Similar to mixed-methods work carried out during the descriptive phase of community needs assessments (Brawner, Reason, Goodman, Schensul, & Guthrie, 2015), research examining how and under what conditions social characteristics are associated with the health and well-being of sexual minority communities in inferential studies is warranted.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that the variation across studies may be ascribed to different historical and contextual characteristics not easily measured through quantitative markers and/or not necessarily replicable across communities. Similar to mixed-methods work carried out during the descriptive phase of community needs assessments (Brawner, Reason, Goodman, Schensul, & Guthrie, 2015), research examining how and under what conditions social characteristics are associated with the health and well-being of sexual minority communities in inferential studies is warranted.…”
Section: Discussionmentioning
confidence: 99%
“…While a city-wide analysis would have been ideal, resources available for the larger study restricted the timeintensive study activities to four census tracts. For the larger investigation, published elsewhere [24], we conducted a multimethod, comparative neighborhoodbased case study in four Philadelphia census tracts on individual-level, social-level, and structural-level factors that contribute to the HIV/AIDS epidemic among black Philadelphians. The larger study included engagement of key stakeholders and an in-depth community ethnography, including field visits, observation, and conversations with residents and business owners, in the four study areas.…”
Section: Data Source and Study Populationmentioning
confidence: 99%
“…Nearly two thirds of the city's cumulative HIV/AIDS cases are among blacks, and in 2014, the number of HIV cases among blacks was almost twice that of whites and Hispanics combined [23]. Brawner et al [24] identified overcrowding, disadvantage, permeability in neighborhood boundaries, and availability and accessibility of health-related resources as primary contributors to these disparities and heightened HIV/AIDS rates in the city. Additionally, Eberhart et al discovered that spatial patterns independently predicted hotspots for poor linkage to care, retention in care, and viral suppression in Philadelphia's HIV/AIDS cases [25].…”
Section: Introductionmentioning
confidence: 99%
“…Several researchers have demonstrated associations between SES and high HIV prevalence (Auerbach, Parkhurst, & C aceres, 2011;Parkhurst, 2010). In geographic mapping studies, researchers have also discovered increased rates of HIV prevalence and high-risk behaviors in low-income neighborhoods (Brawner, Reason, Goodman, Schensul, & Guthrie, 2015;Nunn et al, 2014). Community stressors associated with living in poverty are associated with HIV risk behaviors (Kalichman, Simbayi, Jooste, Cherry, & Cain, 2005).…”
Section: Socioeconomic Statusmentioning
confidence: 99%